Composite skeleton metal-loaded multi-scale molecular sieve nano-catalyst as well as preparation method and application thereof
By using composite skeleton metal-loaded multi-scale molecular sieve nanocatalysts in industrial polluted water treatment, the problems of low treatment efficiency and poor reuse performance in the prior art are solved, and efficient, stable and economical pollution water treatment effects are achieved.
Patent Information
- Application Number
- CN202411866488.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing industrial polluted water treatment technology has problems such as low treatment efficiency, poor reuse performance, high cost, high oxidant content, and the need for high reaction temperature and high system pressure, making it difficult to completely and effectively treat industrial wastewater.
The composite skeleton metal-loaded multi-scale molecular sieve nanocatalyst is used to form multi-scale molecular sieve through glass fibers as a support, and gel technology and steam-assisted synthesis is used to form multi-scale molecular sieve, embedded metal particles to improve catalytic activity, and the metal active components are allowed to enter the molecular sieve framework structure through hydrothermal sieve to avoid the problem of easy enrichment and leaching of active metals.
It improves the catalytic activity, stability and cyclic performance of the catalyst, reduces the risk of secondary pollution, enhances the CO2 selectivity for organic pollutants, and is easy to separate and recover, improving economic benefits.
Smart Images

Figure CN119680618A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a composite skeleton metal-supported multi-scale molecular sieve nanocatalyst and a preparation method and application thereof. Background Art
[0002] Freshwater resources, as one of the necessities for maintaining human and various biological life, have a significant impact on human survival and development. However, with the vigorous development of modern industrial level, the water pollution problem faced by mankind is becoming more and more serious. At present, how to purify and repair industrial polluted water bodies in a green and efficient manner and improve the economic benefits of industrial polluted water treatment is a practical problem that needs to be solved urgently by mankind (Energyenviron.mater, 2021, 4(04): 611-619). At present, scientists have proposed a series of technical means for the separation and purification of industrial wastewater and in-situ remediation, including flocculation sedimentation, biodegradation, selective adsorption and membrane filtration (Chin.J.Chem.Eng, 2023, 59: 222-230). However, these traditional methods generally have disadvantages such as low treatment efficiency and poor reusability, and therefore cannot completely and effectively treat industrial wastewater. For example, the adsorption method has disadvantages such as high cost and low efficiency (J Hazard Mater, 2008, 158: 499-506); biodegradation technology is economical and green, but it is difficult to treat organic pollutants with large differences in biochemical properties and complex structures, and the degradation efficiency is low, and it cannot be applied on a large scale in industry (Appl. Catal. B Environ, 2010, 98 (1): 10-26). Therefore, it is urgent to find an economical, efficient, green and non-toxic water purification technology.
[0003] Advanced oxidation processes (AOPs) are considered to be one of the most effective emerging technologies for water environmental remediation. They have attracted widespread attention due to their strong oxidation ability, efficient reaction rate and wide applicability to the degradation of organic compounds (Chem. Eng. J, 2013, 218: 260-266). However, in their further industrial water purification applications, people found that not all AOP methods are suitable for actual wastewater degradation treatment. Some AOP methods have problems such as large power demand, high oxidant content, and high reaction temperature and high system pressure in actual water purification applications to meet the actual water purification needs (Catalysts, 2018, 8 (12): 673-673). Among the several AOPs currently used for the purification of polluted water bodies, CWO shows great application potential. It changes the reaction process by using efficient and stable catalysts, reduces the temperature and pressure required for the oxidation reaction, and greatly improves the actual water purification treatment effect and oxidation efficiency (Roy. Soc. Open. Sci, 2018, 5 (3): 171731). CWO water purification process can be divided into homogeneous and heterogeneous processes. Among them, the typical homogeneous method, Fenton process, is a common industrial wastewater treatment technology, but it still has defects such as limited pH application range and difficult catalyst recovery (Appl. Catal. A Gen, 2009, 357 (2): 135-141). The heterogeneous process can effectively overcome the above defects, that is, the heterogeneous catalyst that introduces active catalytic components on the carrier material is applied in the polluted water body, which shows the advantages of easy separation and recovery of the catalyst, difficult loss of active components, and green economy of the water purification process (Polymers, 2022, 14 (13): 2749-2749). The selection of carrier materials and the method of introducing active components are also the top priorities of current research.
[0004] Among many carrier materials, molecular sieves have attracted widespread attention due to their unique microstructure and physical and chemical properties. Molecular sieves are a type of aluminosilicate crystals with regular pores. They are composed of silicon and aluminum connected by oxygen bridges to form a skeleton structure. There are many pores with uniform pore sizes and some neatly arranged holes with large internal surface areas in the skeleton structure. This unique microporous structure enables it to play an important role in adsorption, catalysis, separation and other fields (Micropor. Mesopor. Mat, 2022, 331). Among them, ZSM-5 molecular sieve is a type of molecular sieve with a high silicon-aluminum ratio. It has good acid and alkali resistance, good shape selectivity, high specific surface area and a wide silicon-aluminum ratio synthesis range, making its crystal structure easy to control and has been widely used in the chemical industry (J. Environ. Chem. Eng, 2020, 8 (5)). Almghar synthesized a new PANI@Fe-ZSM-5 hybrid composite material through an in situ interfacial polymerization process, which was used for the adsorption treatment reaction of OG dye wastewater. The hybrid composite material not only showed the good redox reversibility and excellent structural stability of PANI, but also showed the excellent adsorption capacity and good reusability of iron-loaded molecular sieves (Chemosphere, 2022 (5): 295); Peng synthesized Pd / Fe-ZSM-5 bimetallic composite catalyst for toluene catalytic emission reduction. Compared with single metal-based catalysts, it showed higher catalytic activity, good service life and water resistance in toluene combustion (Catal. Today, 2019, 332).
[0005] However, the ZSM-5 molecular sieve fiber materials currently used in industry generally have problems such as limited intracrystalline diffusion, pore blockage and severe coking due to the small pore size of their own microporous channels, making it difficult to exert their maximum performance in industrial applications (Chem.Soc.Rev, 2017, 46 (2): 481-558). In recent years, it has been proven feasible to synthesize molecular sieves with hierarchical structures and different levels of porosity for industrial catalytic processes (Ind.Eng.Chem.Res, 2016, 55 (17): 4948-4959). As a member of the multi-level molecular sieve, the multi-scale molecular sieve has a large cavity volume and an interconnected structure of macropores-mesoporous-micropore multi-level channels, which is easy to modify and functionalize, and can effectively reduce the diffusion resistance in the reaction, increase the reaction mass transfer rate, strengthen the efficient heterogeneous catalytic reaction process, and improve the catalytic efficiency and reaction performance of practical applications. In addition, the multi-level channel structure of the multi-scale molecular sieve fiber effectively slows down the carbon deposition rate in the pores and prolongs the service life of the catalyst. The self-supporting structure of multi-scale molecular sieves can also avoid the problems caused by the presence of carriers that affect diffusion and mass transfer, shield active sites, reduce specific surface area and packing density (Chem. Sci, 2016, 7(2): 1582-1587). In current research, there are many methods for preparing multi-scale and multi-level molecular sieve fibers. Dai prepared hollow ZSM-5 single crystals with a silicon-rich surface through a dissolution-recrystallization strategy. However, since this method inevitably involves the treatment of silicon waste and toxic etchants after a time-consuming etching process, it may also lead to product deactivation, loss of active sites, particle aggregation and structural damage (Adv. Funct. Mater, 2015, 25(48): 7479-7487); Ding synthesized a new type of B-ZSM-5 / SS fiber catalyst with a hollow structure in situ through a seed-assisted dry gel gas phase method, avoiding the adverse effects of poor heat transfer and high pressure drop on traditional zeolite particles in a fixed bed reactor. The application of this fiber catalyst in the methanol to propylene reaction significantly improved the reaction efficiency and catalytic activity. However, due to the unsatisfactory additional shedding process during the alkaline leaching process, its service life was also shortened, which was not conducive to the large-scale development of the composite material (Chem. Eng. J, 2018, 361: 588-598).
[0006] At present, most heterogeneous molecular sieve fiber catalysts are usually synthesized by ion exchange or impregnation. Since the binding force between transition metal ions / oxides and the zeolite framework is relatively weak, the existing impregnation and ion exchange methods will cause the introduced active metal heteroatoms to be enriched on the outer surface of the zeolite. In actual applications, leaching and agglomeration of metal ions will occur, resulting in a series of application problems such as secondary pollution, short service life, and poor cycle performance. Summary of the invention
[0007] In order to solve the above technical problems, the present invention proposes a composite skeleton metal-supported multi-scale molecular sieve nanocatalyst and its preparation method and application. The present invention uses glass fiber as a substrate, forms a multi-scale molecular sieve through gel technology and steam-assisted synthesis conversion, utilizes the characteristics of high catalytic performance of metal particles, and simultaneously gives play to the advantages of excellent thermal stability, hydrothermal stability and good shape selectivity of molecular sieves to improve the catalytic activity of the catalyst. The hydrothermal synthesis method is used to allow the metal active components to enter the molecular sieve skeleton structure, avoiding the phenomenon that the introduced active metals are easily enriched and leached due to the traditional impregnation method, thereby solving the defects in a series of application problems such as difficult catalyst recovery, short service life, and low cycle performance. At the same time, the surface acidity of the catalyst can be effectively regulated by optimizing the skeleton metal content through macro-regulation, and it also has the effect of inhibiting the growth of loaded metal grains and maintaining high metal dispersion. Compared with traditional loaded metals, the skeleton metal of the present invention shows higher stability, utilization rate and reaction efficiency in the catalytic process, and has higher CO2 selectivity for the catalytic degradation of organic pollutants. In addition, the metal is loaded on the multi-scale molecular sieve, which solves the problem that the traditional catalyst is difficult to recycle and has low regeneration efficiency, and also increases the contact efficiency between the catalyst and the pollutants in the water body. At the same time, it is easy to separate in the actual use process, improves the recovery efficiency, and avoids the problem of secondary pollution. In short, the composite nanofiber material of the present invention has very good catalytic performance and practical application ability.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention:
[0010] The invention provides a method for preparing a composite skeleton metal-supported multi-scale molecular sieve nanocatalyst, comprising the following steps: mixing tetrapropylammonium hydroxide (TPAOH) with anhydrous ethanol, adding a metal salt at the same time, then adding a silicon source under stirring, crystallizing, and preparing a seed solution; then adding a sodium aluminate (NaAlO2) solution to the seed solution, and then immersing a glass fiber in the seed solution with the NaAlO2 solution added, centrifuging, and drying to obtain a metal skeleton glass fiber loaded with seed crystals; performing steam-assisted crystallization on the metal skeleton glass fiber loaded with seed crystals; drying and calcining the product to remove an organic template, and grinding to obtain the composite skeleton metal-supported multi-scale molecular sieve nanocatalyst.
[0011] The present invention adopts an in-situ solid-solid conversion method, with glass fiber as a carrier material. During the growth of molecular sieve crystals on the carrier material, the carrier material is gradually transformed and removed, and metal ions are embedded in the molecular sieve framework, and finally a skeleton metal multi-scale multi-level molecular sieve with good crystallinity and a self-supporting hierarchical structure is obtained, avoiding the removal of toxic etchants, cleaning silicon sources and other operations, and can effectively improve the mechanical strength and catalytic performance of molecular sieve crystals. In addition, the interaction between the metal compound and the molecular sieve carrier is strong, so that the metal is firmly fixed on the carrier, solving the problem that traditional molecular sieves are easy to agglomerate and leached. At the same time, selecting glass fiber as a carrier material transfers the control of the multi-scale molecular sieve structure from microscopic operation to macroscopic operation, improving the controllability and operability of the multi-scale molecular sieve structure.
[0012] The metal salt includes one of a soluble iron salt, a soluble copper salt, a soluble cobalt salt and a soluble molybdenum salt.
[0013] Exemplarily, the metal salt is one of FeSO4·7H2O, CuSO4·5H2O, CoSO4·7H2O, FeCl2·6H2O, CuCl2·2H2O, CoCl2·6H2O and MoCl3·6H2O.
[0014] The molar ratio of the TPAOH, anhydrous ethanol and silicon source is 10:(10-50):(10-50).
[0015] The silicon source is silicon tetrachloride, silicon dichloride, silane or tetraethyl orthosilicate (TEOS).
[0016] The crystallization temperature is 60-140° C. and the crystallization time is 30-60 hours.
[0017] The mass ratio of the glass fiber to the seed solution is (0.1-1):12, that is, the mass of the glass fiber added to every 12g of seed solution is 0.1-1g.
[0018] The concentration of the NaAlO2 solution is 0.3-0.8 mol / L, and the concentration of the sodium aluminate solution is preferably 0.4 mol / L.
[0019] The immersion time is 10 to 20 hours; and / or
[0020] The centrifugation is: 5-8 r / s for 40-80 s.
[0021] The temperature of the steam-assisted crystallization is 110-200° C. and the time is 15-35 hours; and / or
[0022] The calcination temperature is 450-700°C, the calcination time is 3-8h, preferably the calcination time is 4h; and / or
[0023] The molar ratio of the metal salt to the silicon source is (1:60) to (1:180).
[0024] The second technical solution of the present invention:
[0025] The present invention also provides a composite skeleton metal-supported multi-scale molecular sieve nanocatalyst prepared according to the method.
[0026] The composite skeleton metal-supported multi-scale molecular sieve nanocatalyst prepared by the present invention has good crystallinity and excellent catalytic performance. The metal catalyst has a strong interaction with the carrier. In addition, it has good catalytic effect, high mechanical strength and strong reusability in the actual purification of organic dye wastewater, and gives full play to the excellent performance of each component.
[0027] The third technical solution of the present invention:
[0028] The present invention also provides the use of the composite skeleton metal-supported multi-scale molecular sieve nanocatalyst in removing water pollutants.
[0029] Exemplarily, the pollutant is an organic matter, and the organic matter is preferably an organic matter having an aromatic ring.
[0030] The present invention adopts the synthesis route of in-situ solid phase recrystallization transformation to prepare a molecular sieve nanocatalyst with a multi-scale structure, avoiding the step of processing the substrate material after the crystallization is completed in the traditional preparation method, and can effectively improve the mechanical strength and catalytic performance of the molecular sieve crystal. In the synthesis process of the present invention, the heat treatment time is greatly reduced. At the same time, the present invention adds metal salts during the preparation process in the seed solution, greatly improving the mixing and uniformity of the components, which is conducive to forming a better crystal with composite skeleton metals. At the same time, the present invention embeds the metal active component into the molecular sieve skeleton structure, avoiding the phenomenon that the introduced active metal load is prone to metal ion leaching and agglomeration on the outer surface of the molecular sieve caused by traditional loading, and greatly improving the service life and cycle performance of the catalyst. The composite skeleton metal-loaded multi-scale molecular sieve nanocatalyst of the present invention has high mechanical strength, strong regeneration ability, adjustable metal skeleton, controllable metal loading and loading position, simple method and easy preparation, and has ideal macroscopic structure and catalytic performance. There is a strong interaction between metal compounds and molecular sieves. When applied to actual sewage treatment systems, they can simultaneously give play to the advantages of metal compounds and molecular sieve carriers, improve mass transfer and heat transfer efficiency and contact efficiency, thereby improving catalytic efficiency, and can also make the catalyst firmly bonded to the carrier, reduce the leaching and loss of metal ions, increase the service life of the catalyst, and reduce the regeneration and recovery cost.
[0031] The present invention adopts a hydrothermal synthesis method to allow the metal active components to enter the molecular sieve framework structure to synthesize a multi-scale molecular sieve fiber containing a metal framework, which can avoid the above defects in practical applications. The catalyst surface acidity can be effectively regulated by optimizing the skeleton metal content through macro-adjustment, and it also has the effect of inhibiting the growth of loaded metal grains and maintaining high metal dispersion. At the same time, the skeleton metal shows higher stability, utilization rate and reaction efficiency in the catalytic process compared with the metal outside the skeleton, and has higher CO2 selectivity for the catalytic degradation of organic pollutants.
[0032] Compared with the prior art, the present invention has the following advantages and technical effects:
[0033] (1) Simplified synthesis steps, strong operability. The composite skeleton metal-supported multi-scale molecular sieve nanofiber material of the present invention adopts a direct solvent-free in-situ solid-solid conversion method. Metal salts are introduced when preparing seed crystals. Glass fibers are converted into multi-scale molecular sieves with a porous structure through the hydrolysis and condensation of Si-O-Si bonds. Metal elements exist in the molecular sieve skeleton in the form of ions or atoms, which simplifies the introduction process of metal elements and avoids the need for additional processing of organic waste and removal of carrier materials required by traditional preparation methods. This method is simple, efficient, green and economical. At the same time, according to actual needs, the content of the introduced metal component can be macro-adjusted to control the surface acidity of the catalyst, which has the effect of effectively inhibiting the growth of loaded metal grains and maintaining high metal dispersion, and is easy to put into actual production and application.
[0034] (2) Better physical and chemical properties. The present invention uses a simple hydrothermal synthesis method to introduce metal active components into the multi-scale molecular sieve framework carrier, which solves the problem that the introduced active metal heteroatoms are easily enriched and detached on the outer surface of the zeolite due to the traditional method, avoids the phenomenon of rapid deactivation of the catalyst and secondary pollution, and greatly improves the service life and cycle performance of the product. At the same time, the present invention selects glass fiber as the carrier material, and the synthesized molecular sieve framework contains charge-balancing cations (such as Na + ), this characteristic makes the catalyst surface have more active sites, which can better combine with the reactants in the reaction. In addition, the skeleton metal exists in a different form than the traditional extra-skeleton metal. It forms chemical bonds with other atoms in the molecular sieve framework (such as Si, O, etc.), has a stronger interaction force with the molecular sieve crystal, and also improves the surface charge and acidity of the catalyst. It shows higher stability, utilization and reaction efficiency in the catalytic process, and has higher CO2 selectivity for the catalytic degradation of organic pollutants (that is, the degradation effect is more complete, more methylene blue is converted into CO2 rather than intermediates, and the total organic carbon (TOC) of the reaction system is significantly reduced).
[0035] (3) Higher practical utilization value. The composite skeleton metal-supported multi-scale molecular sieve nanofiber material of the present invention has excellent catalytic performance, strong regeneration ability, low deactivation constant, rich pore size, and strong interaction between the metal component and the molecular sieve carrier. It can simultaneously exert the advantages of the metal active component and the molecular sieve carrier, which not only improves the mass transfer and heat transfer efficiency and contact efficiency, but also reduces the shedding and leaching of metal components, avoids the problem of easy agglomeration of traditional metal catalysts, and improves its application ability in actual production. The composite skeleton metal-supported multi-scale molecular sieve nanofiber material has relatively excellent performance, is easy to synthesize, is flexible to use, and has good industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0037] Figure 1 The microstructure of the composite framework metal-supported multi-scale molecular sieve nanocatalyst prepared in Example 1;
[0038] Figure 2 The crystal morphology and element distribution of the composite framework metal-supported multi-scale molecular sieve nanocatalyst prepared in Example 1. DETAILED DESCRIPTION
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0045] All raw materials used in the embodiments of the present invention are purchased from the market. For example, quartz fiber is purchased from Shanghai Xinhu Experimental Equipment Co., Ltd.; glass fiber is purchased from Shanghai Xinhu Experimental Equipment Co., Ltd.
[0046] In some embodiments of the present invention, a method for preparing a composite skeleton metal-supported multi-scale molecular sieve nanocatalyst is provided, comprising the following steps: mixing tetrapropylammonium hydroxide (TPAOH) with anhydrous ethanol, adding a metal salt at the same time, and then adding a silicon source under stirring, crystallizing, and preparing a seed solution; then adding a sodium aluminate (NaAlO2) solution to the seed solution, and then immersing a glass fiber in the seed solution with the NaAlO2 solution added, centrifuging, and drying to obtain a metal skeleton glass fiber loaded with seeds, performing steam-assisted crystallization on the metal skeleton glass fiber loaded with seeds, and drying and calcining the product to remove the organic template, and grinding to obtain a composite skeleton metal-supported multi-scale molecular sieve nanocatalyst.
[0047] Due to the presence of metal elements in the molecular sieve framework structure, there are cations (such as Na +), this characteristic makes the obtained material have more acidity and active sites, more structural defects, can better combine with reactants in the reaction, and show unique and excellent performance in catalysis and adsorption. In the molecular sieve material prepared by the impregnation method in the prior art, Fe is loaded on the surface of the molecular sieve, which is very easy to form oxides with air, reducing the surface charge of the catalyst and reducing the acidity of the catalyst; and the present invention adds iron element in the process of preparing the seed crystal, and the iron element exists in the molecular sieve framework in the form of ions or atoms after the molecular sieve is formed, and forms chemical bonds with other atoms in the framework (such as Si, O, etc.), so that the charge of the catalyst material as a whole is stronger, which is conducive to the catalytic reaction. The active component Fe of the catalyst prepared by impregnation or ion exchange in the prior art is present on the surface of the molecular sieve, and the interaction force with the carrier is weak, and it is easy to fall off during the reaction, causing the risk of rapid deactivation of the catalyst and secondary pollution. The Fe of the present invention is present in the molecular sieve framework, and remains stable during the reaction, with strong stability. The present invention uses glass fiber as a raw material. In addition to SiO2, there are also some elements such as aluminum oxide, calcium oxide, boron oxide, magnesium oxide, sodium oxide, etc., so that the final molecular sieve has cations, thereby improving the performance of the molecular sieve nanocatalyst.
[0048] In the present invention, since hydrogen peroxide solution (H2O2) is a strong oxidant and is also unstable and easily decomposed into water and oxygen, it will slowly decompose over time, causing it to deteriorate. Therefore, it needs to be prepared and used immediately to ensure accurate concentration and pure solute.
[0049] It should be pointed out that the matters not described in detail in the present invention are all conventional operating means in the art and are not the focus of the present invention. For example, specific methods such as the preparation method of the hydrogen peroxide solution are all completed by conventional methods.
[0050] The present invention adopts the synthesis route of in-situ solid phase recrystallization transformation to prepare a molecular sieve nanocatalyst with a multi-scale structure, avoiding the step of processing the substrate material after the crystallization is completed in the traditional preparation method, and can effectively improve the mechanical strength and catalytic performance of the molecular sieve crystal. In the synthesis process of the present invention, the heat treatment time is greatly reduced. At the same time, the present invention adds metal salts during the preparation process in the seed solution, greatly improving the mixing and uniformity of the components, which is conducive to the formation of crystals with better composite skeleton metals. At the same time, the present invention embeds the metal active component into the molecular sieve skeleton structure, avoiding the phenomenon that the introduced active metal load is prone to metal ion leaching and agglomeration on the outer surface of the molecular sieve caused by traditional loading, and greatly improving the service life and cycle performance of the catalyst. The composite skeleton metal-supported multi-scale molecular sieve nanocatalyst of the present invention has high mechanical strength, strong regeneration ability, adjustable metal skeleton, controllable metal loading and loading position, simple method and easy preparation, and has ideal macroscopic structure and catalytic performance. There is a strong interaction force between the metal compound and the molecular sieve. When applied to the actual sewage treatment system, the advantages of the metal compound and the molecular sieve carrier can be brought into play at the same time, the mass transfer and heat transfer efficiency and the contact efficiency can be improved, thereby improving the catalytic efficiency, and the catalyst can be firmly bonded to the carrier, reducing the leaching loss of metal ions, increasing the service life of the catalyst, and reducing the regeneration and recovery cost. The composite skeleton metal-supported multi-scale molecular sieve nanocatalyst of the present invention can efficiently remove water pollutants, especially organic matter with aromatic rings. The preparation method of the present invention is highly operable, and the prepared material can simultaneously bring into play the advantages of nano metals and multi-scale porous molecular sieves, with the advantages of large specific surface area, high crystallinity and stable structure. In actual water purification applications, it can solve the shortcomings of easy oxidation, easy agglomeration and difficult recovery of nano metal particles, and can also improve the mass transfer and heat transfer efficiency and catalytic efficiency, which is conducive to its better performance in catalysis. In some typical embodiments of the present invention, methylene blue is used as an example for illustration.
[0051] In an embodiment of the present invention, the calculation method of the methylene blue degradation rate is as follows: the absorbance of the solution is measured by a UV-visible spectrophotometer, and the methylene blue degradation rate (%) is calculated according to the formula: (initial absorbance-absorbance) / initial absorbance×100%; the calculation method of the metal ion leaching concentration is as follows: metal ion leaching concentration (mg / L)=dilution factor×data value measured by inductively coupled plasma emission spectroscopy.
[0052] The technical solution of the present invention is further illustrated by the following embodiments.
[0053] Example 1
[0054] A method for preparing a composite framework iron-supported multi-scale molecular sieve nanocatalyst:
[0055] (1) Preparation of Seed Solution from Seed Gel
[0056] (1-1) Take out a dry and clean beaker, pour 8.8 g (0.0108 mol) of TPAOH (25 wt.% aqueous solution) and 2 g (0.0435 mol) of ETOH (anhydrous ethanol) weighed in advance into the beaker, then add 0.1103 g (0.0004 mol) of FeSO4·7H2O as an iron source into the beaker to prepare skeleton iron, place the beaker on a magnetic stirrer, and add 9.92 g (0.0476 mol) of TEOS dropwise while stirring;
[0057] (1-2) Take another dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 °C and allow it to crystallize for 48 h. After cooling, a seed solution of 25TPAOH / 110SiO2 / 853.45H2O / 100ETOH / 0.92Fe is obtained, which can be directly used;
[0058] The calculation process of seed solution preparation is as follows:
[0059] M(TPAOH)=203.36 g / mol, m(TPAOH (25% aqueous solution))=8.8 g, n(TPAOH)=(8.8*25%) / 203.36=0.010818 mol, n(H2O)=(8.8*75%) / 18=0.366667 mol;
[0060] M(TEOS)=208.33 g / mol, m(TEOS)==9.92 g (containing 1 molecule of Si), n(SiO2)=9.92 /
[0061] 208.33 = 0.047617 mol;
[0062] M(EtOH)=46.07g / mol, m(EtOH)=2g, n(EtOH)=2 / 46.07=0.043412mol;
[0063] M(FeSO4·7H2O)=278.01g / mol, m(FeSO4·7H2O)=0.1103g, n(Fe)=0.1103 /
[0064] 278.01=0.000397mol, n(H2O)=(7*0.1103) / 278.01=0.002777mol;
[0065] a TPAOH=b SiO2=x H2O=y EtOH=z Fe. Let b=110, then a=(110*0.010818) /
[0066] 0.047617≈25; x=(110*(0.366667+0.002777)) / 0.047617≈853.45; y=(110*0.043412) / 0.047617≈100; z=(110*0.000397) / 0.047617≈0.92. So the result is 25TPAOH / 110SiO2 / 853.45H2O / 100ETOH / 0.92Fe.
[0067] (2) Preparation of seed-loaded glass fiber by impregnation method
[0068] (2-1) Add 1 g of deionized water and 0.0325 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0069] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0070] (3) Preparation of composite framework iron-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0071] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, and then place the liner in an oven for steam-assisted crystallization at 150 °C for 24 h.
[0072] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0073] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework iron-supported multi-scale molecular sieve nanocatalyst.
[0074] The microstructure of the composite skeleton metal-supported multi-scale molecular sieve nanocatalyst prepared in Example 1 is shown in FIG. Figure 1 , crystal morphology and element distribution are shown in Figure 2 .from Figure 2It can be seen that Si, Al, and O elements are evenly distributed on the surface of the molecular sieve fiber, proving that the prepared sample has good crystallinity, and Fe elements are also evenly distributed in the molecular sieve, indicating that the metal ions of the catalyst of the present invention are successfully embedded in the molecular sieve framework. Figure 1 It can be seen that the molecular sieve nanocatalyst has good crystallinity, and the lamellar molecular sieve crystals are stacked to form a self-supporting hierarchical structure. The thickness of the molecular sieve layer reaches more than 3μm, which makes the fiber structure stable and has more active sites. The microporous structure of the molecular sieve crystal itself, the mesoporous structure formed by crystal stacking, and the intermediate macroporous structure together constitute the multi-level structure of the composite skeleton metal-supported multi-scale molecular sieve nanocatalyst, giving it excellent catalytic performance.
[0075] Composite framework iron-supported multi-scale molecular sieve nanocatalyst has important application in wastewater treatment field, and it can firmly load and reduce metal ion loss. The composite framework iron-supported multi-scale molecular sieve composite nanofiber material catalytic degradation initial concentration is 10mg / L methylene blue solution. Add 20mL 50mg / L methylene blue solution, 0.2g / L composite framework iron-supported multi-scale molecular sieve nanocatalyst (i.e. the concentration of molecular sieve nanocatalyst in mixed solution is 0.2g / L, the same below) prepared by this implementation into a dry and clean beaker, 25mL 20mmol / L newly made hydrogen peroxide solution (i.e. hydrogen peroxide solution is now prepared and used) and 55mL deionized water, obtain 100mL mixed solution, the mixed solution is vibrated at 200rpm rotating speed for 30min, finally the degradation rate of methylene blue obtained by testing reaches 95% (TOC conversion rate=80%), and the iron ion leaching concentration in the composite framework iron-supported multi-scale molecular sieve nanocatalyst is less than 2mg / L. At the same time, the catalyst after the reaction was dried and the experiment was repeated. After 5 cycles, the degradation rate of methylene blue still reached more than 90% (TOC conversion rate>70%), indicating that the catalyst has good stability.
[0076] Example 2
[0077] A method for preparing a composite framework copper-supported multi-scale molecular sieve nanocatalyst:
[0078] (1) Preparation of Seed Solution from Seed Gel
[0079] (1-1) Take out a dry and clean beaker, pour 8.6 g (0.0106 mol) of TPAOH (25 wt.% aqueous solution) and 1.8 g (0.0391 mol) of ETOH weighed in advance into the beaker, then add 0.0986 g (0.0004 mol) of CuSO4·5H2O as a copper source into the beaker to prepare skeleton copper, place the beaker on a magnetic stirrer, and add 9.88 g (0.0474 mol) of TEOS dropwise while stirring;
[0080] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 ° C and allow it to crystallize for 48 h. After cooling, a seed solution of 24.52TPAOH / 110SiO2 / 835.72H2O / 90.62ETOH / 0.92Cu is obtained, which can be directly used;
[0081] (2) Preparation of seed-loaded glass fiber by impregnation method
[0082] (2-1) Add 1 g of deionized water and 0.0324 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0083] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0084] (3) Preparation of composite framework copper-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0085] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and perform steam-assisted crystallization at 150 °C for 24 h.
[0086] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0087] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework copper-supported multi-scale molecular sieve nanocatalyst.
[0088] Composite skeleton copper-supported multi-scale molecular sieve composite nanofiber material has important applications in the field of wastewater treatment. It can firmly load and reduce the loss of metal ions. The composite skeleton copper-supported multi-scale molecular sieve composite nanofiber material prepared in this embodiment can be used to catalyze the degradation of a methylene blue solution with an initial concentration of 10 mg / L. Add 20 mL 50 mg / L methylene blue solution, 0.2 g / L catalyst, 25 mL 20 mmol / L fresh hydrogen peroxide solution and 55 mL deionized water to a dry and clean beaker to obtain 100 mL of a mixed solution, and the mixed solution is vibrated at 200 rpm for 30 min. Finally, the degradation rate of methylene blue can be obtained by testing to reach 95.8% (TOC conversion rate = 78.5%), and the copper ion leaching concentration is less than 1.97 mg / L. At the same time, the catalyst after the reaction is dried and repeated experiments are carried out. After 5 cycles, the degradation rate of methylene blue still reaches more than 90% (TOC conversion rate> 70%), indicating that the catalyst has good stability.
[0089] Example 3
[0090] A method for preparing a composite framework cobalt-supported multi-scale molecular sieve nanocatalyst:
[0091] (1) Preparation of Seed Solution from Seed Gel
[0092] (1-1) Take out a dry and clean beaker, pour 9.0 g (0.0111 mol) of TPAOH (25 wt.% aqueous solution) and 2.2 g (0.0478 mol) of ETOH weighed in advance into the beaker, then add 0.1111 g (0.0004 mol) of CoSO4·7H2O as a cobalt source into the beaker to prepare framework cobalt, place the beaker on a magnetic stirrer, and add 9.88 g (0.0474 mol) of TEOS dropwise while stirring;
[0093] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 °C and allow it to crystallize for 48 h. After cooling, a seed solution of 25.66TPAOH / 110SiO2 / 876.21H2O / 110.75ETOH / 0.92Co is obtained, which can be directly used;
[0094] (2) Preparation of seed-loaded glass fiber by impregnation method
[0095] (2-1) Add 1 g of deionized water and 0.0324 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0096] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0097] (3) Preparation of composite framework cobalt-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0098] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and perform steam-assisted crystallization at 150 °C for 24 h.
[0099] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0100] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework cobalt-supported multi-scale molecular sieve nanocatalyst.
[0101] Composite framework cobalt-loaded multi-scale molecular sieve composite nanofiber material has important applications in the field of wastewater treatment. It can firmly load and reduce the loss of metal ions. The composite framework cobalt-loaded multi-scale molecular sieve composite nanofiber material prepared in this embodiment can be used to catalyze the degradation of a methylene blue solution with an initial concentration of 10 mg / L. Add 20 mL 50 mg / L methylene blue solution, 0.2 g / L catalyst, 25 mL 20 mmol / L fresh hydrogen peroxide solution and 55 mL deionized water to a dry and clean beaker to obtain 100 mL of a mixed solution, and the mixed solution is oscillated at 200 rpm for 30 min. Finally, it is detected that the degradation rate of methylene blue reaches 95.6% (TOC conversion rate = 80.2%), and the cobalt ion leaching concentration is less than 1.9 mg / L. At the same time, the catalyst after the reaction is dried and repeated experiments are carried out. After 5 cycles, the degradation rate of methylene blue still reaches more than 90% (TOC conversion rate> 70%), indicating that the catalyst has good stability.
[0102] Example 4
[0103] A method for preparing a composite framework iron-supported multi-scale molecular sieve nanocatalyst:
[0104] (1) Preparation of Seed Solution from Seed Gel
[0105] (1-1) Take out a dry and clean beaker, pour 8.7 g (0.0107 mol) of TPAOH (25 wt.% aqueous solution) and 1.9 g (0.0412 mol) of ETOH weighed in advance into the beaker, then add 0.0934 g (0.0004 mol) of FeCl2·6H2O as an iron source to the beaker to prepare skeleton iron, place the beaker on a magnetic stirrer, and add 9.92 g (0.0476 mol) of TEOS dropwise while stirring;
[0106] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 ° C and allow it to crystallize for 48 h. After cooling, a seed solution of 24.71TPAOH / 110SiO2 / 842.91H2O / 95.27ETOH / 0.92Fe is obtained, which can be directly used;
[0107] (2) Preparation of seed-loaded glass fiber by impregnation method
[0108] (2-1) Add 1 g of deionized water and 0.0325 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0109] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0110] (3) Preparation of composite framework iron-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0111] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and perform steam-assisted crystallization at 150 °C for 24 h.
[0112] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0113] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework iron-supported multi-scale molecular sieve nanocatalyst.
[0114] Composite framework iron-loaded multi-scale molecular sieve composite nanofiber material has important applications in the field of wastewater treatment. It can firmly load and reduce the loss of metal ions. The composite framework iron-loaded multi-scale molecular sieve composite nanofiber material prepared by the present embodiment can be used to catalyze the degradation of a methylene blue solution with an initial concentration of 10mg / L. 20mL50mg / L methylene blue solution, 0.2g / L catalyst, 25mL 20mmol / L fresh hydrogen peroxide solution and 55mL deionized water are added to a dry and clean beaker to obtain 100mL of a mixed solution, the mixed solution is vibrated at 200rpm for 30min, and finally the degradation rate of methylene blue obtained by testing reaches 94.8% (TOC conversion rate = 80%), and the iron ion leaching concentration is less than 2.18mg / L. At the same time, the catalyst after the reaction is dried and repeated experiments are carried out, and the degradation rate of methylene blue still reaches more than 90% (TOC conversion rate> 70%) after 5 cycles, indicating that the catalyst has good stability.
[0115] Example 5
[0116] A method for preparing a composite framework copper-supported multi-scale molecular sieve nanocatalyst:
[0117] (1) Preparation of Seed Solution from Seed Gel
[0118] (1-1) Take out a dry and clean beaker, pour 8.75 g (0.0108 mol) of TPAOH (25 wt.% aqueous solution) and 1.83 g (0.0391 mol) of ETOH weighed in advance into the beaker, then add 0.0669 g (0.0004 mol) of CuCl2·2H2O as a copper source into the beaker to prepare skeleton copper, place the beaker on a magnetic stirrer, and add 9.83 g (0.0470 mol) of TEOS dropwise while stirring;
[0119] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 ° C and allow it to crystallize for 48 h. After cooling, a seed solution of 25.15TPAOH / 110SiO2 / 854.39H2O / 92.89ETOH / 0.92Cu is obtained, which can be directly used;
[0120] (2) Preparation of seed-loaded glass fiber by impregnation method
[0121] (2-1) Add 1 g of deionized water and 0.0321 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0122] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0123] (3) Preparation of composite framework copper-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0124] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and perform steam-assisted crystallization at 150 °C for 24 h.
[0125] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0126] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework copper-supported multi-scale molecular sieve nanocatalyst.
[0127] Composite skeleton copper-supported multi-scale molecular sieve composite nanofiber material has important applications in the field of wastewater treatment. It can firmly load and reduce the loss of metal ions. The composite skeleton copper-supported multi-scale molecular sieve composite nanofiber material prepared in this embodiment can be used to catalyze the degradation of a methylene blue solution with an initial concentration of 10 mg / L. Add 20 mL 50 mg / L methylene blue solution, 0.2 g / L catalyst, 25 mL 20 mmol / L fresh hydrogen peroxide solution and 55 mL deionized water to a dry and clean beaker to obtain 100 mL of a mixed solution, and the mixed solution is oscillated at 200 rpm for 30 min. Finally, it is detected that the degradation rate of methylene blue reaches 95.5% (TOC conversion rate = 78.3%), and the copper ion leaching concentration is less than 2 mg / L. At the same time, the catalyst after the reaction is dried and repeated experiments are carried out. After 5 cycles, the degradation rate of methylene blue still reaches more than 90% (TOC conversion rate> 70%), indicating that the catalyst has good stability.
[0128] Example 6
[0129] A method for preparing a composite framework cobalt-supported multi-scale molecular sieve nanocatalyst:
[0130] (1) Preparation of Seed Solution from Seed Gel
[0131] (1-1) Take out a dry and clean beaker, pour 8.77 g (0.0108 mol) of TPAOH (25 wt.% aqueous solution) and 1.93 g (0.0419 mol) of ETOH weighed in advance into the beaker, then add 0.0945 g (0.0004 mol) of CoCl2·6H2O as a cobalt source into the beaker to prepare framework cobalt, place the beaker on a magnetic stirrer, and add 9.91 g (0.0476 mol) of TEOS dropwise while stirring;
[0132] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 °C and allow it to crystallize for 48 h. After cooling, a seed solution of 24.93TPAOH / 110SiO2 / 850.47H2O / 96.87ETOH / 0.92Co is obtained, which can be directly used;
[0133] (2) Preparation of seed-loaded glass fiber by impregnation method
[0134] (2-1) Add 1 g of deionized water and 0.0325 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0135] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0136] (3) Preparation of composite framework cobalt-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0137] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and perform steam-assisted crystallization at 150 °C for 24 h.
[0138] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0139] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework cobalt-supported multi-scale molecular sieve nanocatalyst.
[0140] Composite framework cobalt-loaded multi-scale molecular sieve composite nanofiber material has important applications in the field of wastewater treatment. It can firmly load and reduce the loss of metal ions. The composite framework cobalt-loaded multi-scale molecular sieve composite nanofiber material prepared in this embodiment can be used to catalyze the degradation of a methylene blue solution with an initial concentration of 10 mg / L. Add 20 mL 50 mg / L methylene blue solution, 0.2 g / L catalyst, 25 mL 20 mmol / L fresh hydrogen peroxide solution and 55 mL deionized water to a dry and clean beaker to obtain 100 mL of a mixed solution, and the mixed solution is oscillated at 200 rpm for 30 min. Finally, the degradation rate of methylene blue can be obtained by testing to reach 96.1% (TOC conversion rate = 77.3%), and the cobalt ion leaching concentration is less than 1.89 mg / L. At the same time, the catalyst after the reaction is dried and repeated experiments are carried out. After 5 cycles, the degradation rate of methylene blue still reaches more than 90% (TOC conversion rate> 70%), indicating that the catalyst has good stability.
[0141] Example 7
[0142] A method for preparing a composite framework molybdenum-supported multi-scale molecular sieve nanocatalyst:
[0143] (1) Preparation of Seed Solution from Seed Gel
[0144] (1-1) Take out a dry and clean beaker, pour 8.95 g (0.0110 mol) of TPAOH (25 wt.% aqueous solution) and 2.11 g (0.0458 mol) of ETOH weighed in advance into the beaker, then add 0.1086 g (0.0004 mol) of MoCl3·6H2O as a molybdenum source into the beaker to prepare skeleton molybdenum, place the beaker on a magnetic stirrer, and add 9.93 g (0.0477 mol) of TEOS dropwise while stirring;
[0145] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 ° C and allow it to crystallize for 48 h. After cooling, a seed solution of 25.39TPAOH / 110SiO2 / 866.11H2O / 105.70ETOH / 0.92Mo is obtained, which can be directly used;
[0146] (2) Preparation of seed-loaded glass fiber by impregnation method
[0147] (2-1) Add 1 g of deionized water and 0.0326 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0148] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0149] (3) Preparation of composite framework molybdenum-supported multi-scale molecular sieve catalyst by steam-assisted crystallization
[0150] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and perform steam-assisted crystallization at 150 °C for 24 h.
[0151] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0152] (3-3) The temperature was raised to 500 °C at a rate of 1 °C / min in a muffle furnace, kept at this temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a composite framework molybdenum-supported multi-scale molecular sieve nanocatalyst.
[0153] Composite framework molybdenum-supported multi-scale molecular sieve composite nanofiber material has important applications in the field of wastewater treatment. It can firmly load and reduce the loss of metal ions. The composite framework molybdenum-supported multi-scale molecular sieve composite nanofiber material prepared in this embodiment can be used to catalyze the degradation of a methylene blue solution with an initial concentration of 10mg / L. Add 20mL50mg / L methylene blue solution, 0.2g / L catalyst, 25mL 20mmol / L fresh hydrogen peroxide solution and 55mL deionized water to a dry and clean beaker to obtain 100mL of a mixed solution, and the mixed solution is oscillated at 200rpm for 30min. Finally, the degradation rate of methylene blue can be obtained by testing to reach 95.3% (TOC conversion rate = 79.3%), and the molybdenum ion leaching concentration is less than 1.96mg / L. At the same time, the catalyst after the reaction is dried and repeated experiments are carried out. After 5 cycles, the degradation rate of methylene blue still reaches more than 90% (TOC conversion rate> 70%), indicating that the catalyst has good stability.
[0154] Comparative Example 1
[0155] The method is the same as Example 1, except that in step (2-1), quartz fiber is impregnated into the seed gel, that is, quartz fiber is used instead of glass fiber in this comparative example.
[0156] The results show that compared with Example 1, the degradation rate of the framework iron-supported multi-scale molecular sieve nanocatalyst prepared in this comparative example in the catalytic oxidation degradation of methylene blue reaction under the same conditions is 80% (TOC conversion rate = 53%), and the degradation rate is low.
[0157] Comparative Example 2
[0158] The same as Example 1, the only difference is that 0.0651 g (0.0008 mol) of NaAlO2 is added in step (2-1).
[0159] The results show that compared with Example 1, the molecular sieve nanocatalyst prepared in this comparative example has a looser structure.
[0160] The performance of the molecular sieve nanocatalyst prepared in this comparative example was tested in the same manner as in Example 1. Compared with Example 1, the degradation rate of the molecular sieve nanocatalyst prepared in this comparative example in the catalytic oxidation degradation of methylene blue reaction under the same conditions was 83% (TOC conversion rate = 42.5%), and the degradation rate was low.
[0161] Comparative Example 3
[0162] The same as Example 1, the only difference is that FeSO4·7H2O is not introduced in step (1-1).
[0163] The results show that the multi-scale molecular sieve nanocatalyst prepared in this comparative example has uniform pores and high mechanical strength.
[0164] The performance of the molecular sieve nanocatalyst prepared in this comparative example was tested in the same manner as in Example 1. Compared with Example 1, the degradation rate of the molecular sieve nanocatalyst prepared in this comparative example in the catalytic oxidation degradation of methylene blue reaction under the same conditions was 30% (TOC conversion rate = 7%), which was a low degradation rate.
[0165] Comparative Example 4 Traditional Dipping Method
[0166] (1) Preparation of Seed Solution from Seed Gel
[0167] (1-1) Take out a dry and clean beaker, pour 8.8 g (0.0108 mol) of TPAOH (25 wt.% aqueous solution) and 2 g (0.0435 mol) of ETOH weighed in advance into the beaker, place the beaker on a magnetic stirrer, and add 9.92 g (0.0476 mol) of TEOS dropwise while stirring;
[0168] (1-2) Take a dry and clean blue-mouth bottle with a volume of 100 mL, pour the mixed solution in the beaker into it, place the blue-mouth bottle on a magnetic stirrer and stir it for 6 h, then put it in an oven set to 100 °C and allow it to crystallize for 48 h. After cooling, a seed solution of 25TPAOH / 110SiO2 / 853.42H2O / 100ETOH that can be directly used is obtained;
[0169] (2) Preparation of seed-loaded glass fiber by impregnation method
[0170] (2-1) Add 1 g of deionized water and 0.0325 g (0.0004 mol) of NaAlO2 to a dry and clean beaker, stir with a glass rod, then add the mixture to 12 g of the seed solution and stir. Use tweezers to immerse 0.5 g of glass fiber into the gel for 12 h.
[0171] (2-2) Place the impregnated glass fiber into a centrifuge tube, set the speed of the centrifuge to 6 r / s, and set the time to 1 min to remove the excess seed crystals in the cavities of the glass fiber. Take out the glass fiber and dry it in an oven at 80°C for 12 hours.
[0172] (3) Preparation of multi-scale molecular sieve catalysts
[0173] (3-1) Use tweezers to tear up the seeded glass fiber and place it in a raised polytetrafluoroethylene support located in the middle of the polytetrafluoroethylene liner of an 80 mL reactor. Pour 4 mL of distilled water at the bottom of the liner, then place the liner in an oven and crystallize at 150 °C for 24 h.
[0174] (3-2) After cooling to room temperature, the product was dried at 110°C overnight;
[0175] (3-3) The temperature was raised to 500 °C in a muffle furnace at a rate of 1 °C / min, kept at that temperature for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a multiscale molecular sieve nanocatalyst.
[0176] (4) Preparation of iron-based multi-scale molecular sieve nanocatalysts
[0177] (4-1) Weigh 0.359 g of ferrous sulfate into a beaker, add deionized water and stir until completely dissolved. Transfer to a 100 mL volumetric flask for later use (concentration is 2.36 × 10 -2 mol / L);
[0178] (4-2) Weigh 0.4875 g of molecular sieve powder into a 250 mL blue-mouth bottle, add 100 mL of the above solution, sonicate for 30 min, and then dropwise add 25 mL of 0.5 mol / L NaOH solution;
[0179] (4-3) The solution was shaken at 200 rpm for half an hour, filtered, and dried at 120 °C for 2 h to obtain an iron-based multi-scale molecular sieve composite nanocatalyst.
[0180] The performance of the iron-based multi-scale molecular sieve nanocatalyst prepared in this comparative example was tested in the same manner as in Example 1. Compared with Example 1, the iron-based multi-scale molecular sieve nanocatalyst prepared in this comparative example had a degradation rate of 90% in the catalytic oxidation degradation of methylene blue under the same conditions, but the TOC conversion rate was only 56.3%, and the iron ion leaching concentration reached 20 mg / L. At the same time, after 5 cycles, the degradation rate of methylene blue was reduced to 50%, and the TOC conversion rate was <10%.
[0181] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a composite framework metal-supported multi-scale molecular sieve nanocatalyst, characterized in that: The following steps are involved: Tetrapropylammonium hydroxide and anhydrous ethanol are mixed, a metal salt is added at the same time, and then a silicon source is added under stirring to crystallize and prepare a seed solution; Then, a sodium aluminate solution is added to the seed solution, and then the glass fiber is immersed in the seed solution with the sodium aluminate solution added, centrifuged, and dried to obtain a metal skeleton glass fiber loaded with seed crystals; the metal skeleton glass fiber loaded with seed crystals is subjected to steam-assisted crystallization; the product is dried, calcined, and ground to obtain the composite skeleton metal-loaded multi-scale molecular sieve nanocatalyst.
2. The method for preparing the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 1, characterized in that: The metal salt includes one of a soluble iron salt, a soluble copper salt, a soluble cobalt salt and a soluble molybdenum salt.
3. The method for preparing the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 1, characterized in that: The molar ratio of the tetrapropylammonium hydroxide, anhydrous ethanol and silicon source is 10:(10-50):(10-50).
4. The method for preparing the composite skeleton metal-supported multi-scale molecular sieve nanocatalyst according to claim 3, characterized in that: The silicon source is silicon tetrachloride, silicon dichloride, silane or ethyl orthosilicate.
5. The method for preparing the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 1, characterized in that: The crystallization temperature is 60-140° C. and the crystallization time is 30-60 hours.
6. The method for preparing the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 1, characterized in that: The concentration of the sodium aluminate solution is 0.3-0.8 mol / L.
7. The method for preparing the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 1, characterized in that: The immersion time is 10 to 20 hours; and / or The centrifugation is: 5-8 r / s for 40-80 s.
8. The method for preparing the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 1, characterized in that: The temperature of the steam-assisted crystallization is 110-200° C. and the time is 15-35 hours; and / or The calcination temperature is 450-700°C and the calcination time is 3-8h; and / or The molar ratio of the metal salt to the silicon source is (1:60) to (1:180).
9. A composite framework metal-supported multi-scale molecular sieve nanocatalyst, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the composite framework metal-supported multi-scale molecular sieve nanocatalyst according to claim 9 in removing water pollutants.
Citation Information
Patent Citations
Gradient composite molecular sieve membrane catalytic material and preparation method and application thereof
CN102861609A
Glass fiber loading cuprous oxide visible light catalyst and application thereof
CN103191738A
Multi-component photocatalytic material of zeolite modified glass fibers, and preparation method and application thereof
CN109647496A
Molecular sieve supported metal catalyst and preparation method thereof
CN113441175A
Preparation method of efficient and stable multi-layer molecular sieve hollow fiber catalytic membrane
CN114570436A